Distribution of rheumatological diseases in rural and urban areas: An adapted COPCORD Stage I Phase III survey of Lucknow district in north India. (4th September 2018) - Kumar, Puneet; Alok, Ragini; Das, Siddharth K.; Srivastava, Ragini; Agarwal, Girdhar G.
Abstract: Objectives: To study the distribution of various rheumatological diseases in rural and urban areas of Lucknow, India. Method: A study using adapted a Community Oriented Program for the Control of Rheumatic Diseases scheme was carried out in a cluster of rural (n = 5118) and urban (n = 5053) communities through a door‐to‐door survey. Trained community volunteers completed the questionnaires. Patients with musculoskeletal pain (MSK pain) were clinically evaluated by a physician. X‐ray examinations and blood investigations were also done. Diagnosis was made according to International Classification of Diseases‐9 classification system. Results: Among persons reporting MSK pain in rural areas, high prevalence of osteoarthritis (OA) knee (35%) was observed followed by fibromyalgia (32.1%), backache (28.4%), non‐specific pain (NSP) (20.7%) and rheumatoid arthritis (RA) (1.2%). In urban area, OA knee (36.3%) and backache (36.6%) were found highly prevalent, followed by fibromyalgia (11.1%), NSP (10.9%) and neck pain (7.4%). In urban areas among MSK pain patients, prevalence of RA was only 1.6%. Age‐adjusted analysis among urban people showed backache complaints begin early (>20 years) than rural people. Significantly higher numbers of Knee OA complaints emerged among urban people than rural in the age group 21‐60 years. Projected population prevalence of knee OA was 44.9 and 106.07/1000 in rural and urban areas, respectively. Further projected population prevalences of fibromyalgia, backache, RA and NSP in rural and urban areas are 41.2 and 32.4, 36.5 and 106.6, 1.56 and 4.74, 26.0 and 32.0 per 1000, respectively. Conclusion: OA knee, fibromyalgia, backache and NSP are predominant health problems of both areas. Female preponderance was observed in all rheumatological diseases in both the areas.